Budaya Literasi Media Digital Pada Ibu-Ibu Rumah Tangga - Dewi Novianti; Siti Fatonah (Universitas Andalas, 2019)
Media literacy in the digital era has become important. Various layers of society need to understand the importance of digital media literacy. Research subjects were housewives in the Sleman area of Yogyakarta. Research subjects so far have not understood how to intelligently consume media. Media content worries that most of them are negative which can anesthetize the audience. The biggest content from media is entertainment. The media prioritizes entertainment programs that pay less attention to the ethics and norms of society. They don't care about the negative impact of the content displayed. Thus it is necessary to cultivate the media literacy movement for housewives. The method used is content analysis, literature study, in-depth interviews, observation, and FGD. The results of the study show that housewives after being given training, socialization, and FGD on digital media literacy became aware of the importance of digital media literacy. Then they continuously convey to the family and the environment where they are. On several occasions, PKK meetings, the Qur’an recitation group, socialized the importance of digital media literacy. Finally, this digital media literacy becomes a culture especially in Maguwoharjo Village, Sleman regency, Yogyakarta. This village is a pilot village of digital media literacy culture for the surrounding environment, especially the Sleman Regency Yogyakarta.